Overview Of The Crime Of Management Of Severe Massage - Julaeha Kamaru (Estudiante Law Journal, 2021)
This study aims to determine the handling of the crime of severe persecution. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling. The results of this study indicate that non-criminal mistreatment is carried out in two stages, namely preventive countermeasures and repressive countermeasures. As for preventive countermeasures, there are several things that are carried out by law enforcers which are to prevent the occurrence of criminal acts of persecution, especially the type of severe abuse, including those carried out in this preventive stage such as legal counseling, patrols in certain areas and conducting bhabinkamtibmas. Meanwhile, in the repressive countermeasures stage, it is certainly the final action taken by law enforcement to prevent the occurrence of criminal acts of persecution. In this countermeasure stage, law enforcers must carry out legal process actions according to procedures if there are violations of the provisions of the applicable laws and regulations. The Gorontalo City Government is also expected to be able to contribute in dealing with the problem of criminal acts whose perpetrators deserve the appropriate punishment, also because considering this severe persecution is very influential in people's lives.